Formulation of Indigenous Bacterial Consortium From Salt Wastewater (Bittern) in Degrading Plastic - Abdus Salam Junaedi; Maftuh Ahnan; Putri Wahyuningtyas; Muhammad Zainuri; Haryo Triajie (Airlangga Journal of Innovation Management, 2026)
Plastic is classified as a synthetic polymer with a long and repetitive chain structure, making its decomposition process very slow. This study aims to measure the optical density (OD) value, determine the total plate count (TPC) value, and compare the plastic degradation activity between the indigenous bacterial formulation from salt washing wastewater and the control bacterial formulation. The optical density (OD) values of the indigenous bacteria from salt washing wastewater (bittern) in degrading plastic waste in Yeast Extract Broth (YEB) + 0.1% glucose medium by formulations F1, F2, F3, and F4 after 7 days of incubation were 1.595, 1.592, 1.488, and 1.645, respectively. The total plate count (TPC) values of the indigenous bacteria from salt washing wastewater (bittern) in degrading plastic waste in Yeast Extract Broth (YEB) + 0.1% glucose medium by formulations F1, F2, F3, and F4 after 7 days of incubation were 13.66 Log CFU/mL, 13.66 Log CFU/mL, 13.73 Log CFU/mL, and 13.62 Log CFU/mL, respectively. The percentage of plastic dry weight after 7 days of incubation in Yeast Extract Broth (YEB) + 0.1% glucose medium produced by indigenous bacteria from salt washing wastewater (bittern) F1, F2, F3, and F4 were 10.43%, 40%, 15.89%, and 15.68%, respectively. This study demonstrates the potential of indigenous bacterial formulations from salt washing wastewater (bittern) as effective plastic biodegradation agents, contributing positively to the development of environmental biotechnology, and serving as a reference for industries and policymakers in promoting sustainable plastic waste management.